The birth of epigraphic culture in the western Mediterranean: Sicilian epigraphic culture in the later Hellenistic period - Prag, J (Consejo Superior de Investigaciones Científicas, 2018)
Sicily has a vibrant and individual epigraphic culture from the Archaic period onwards. Using the data available from the I.Sicily project, this paper surveys the epigraphic culture of the island in order to contextualise and analyse epigraphic practice on the island in the Hellenistic period. The material is predominantly Greek in this period, with a minor presence of Punic, Oscan, and Latin. Analysis concentrates on lapidary epigraphy, but includes a discussion of bronze epigraphy and honorific practices on bronze, which show distinctive local features. Epigraphic practices on the island, and the linguistic evidence in particular, suggests an independent and distinctively Sicilian epigraphic tradition that belongs within the wider Hellenistic Mediterranean context and is almost wholly unaffected by Roman practices until the Augustan period.